Preparation of hybrid porcine thymus containing non‐human primate thymic epithelial cells in miniature swine. (10th July 2019) - Sekijima, Mitsuhiro; Sahara, Hisashi; Shimizu, Akira; Iwanaga, Takehiro; Murokawa, Takahiro; Ariyoshi, Yuichi; Pomposelli, Thomas; Khosravi Maharlooei, Mohsen; Sykes, Megan; Yamada, Kazuhiko
Abstract: Background: We have achieved greater than a 6‐month survival of a life‐supporting kidney co‐transplanted with a vascularized thymic graft into non‐human primates (NHPs). Although we have achieved pig‐specific unresponsiveness in vitro, immunosuppression was not able to be fully weaned. Studies in mice and humanized mice suggest that a hybrid pig thymus (Hyb‐thy)‐containing host thymic epithelial cells (TECs) can optimize intra‐thymic selection, achieving xenograft tolerance with improved reconstitution of T‐cell function. Methods: We have tested the feasibility of the preparation of a Hyb‐thy that contains NHP TECs in the donor thymic grafts. We first prepared the Hyb‐thy in the donor pigs 2‐3 weeks before xeno‐Tx. We performed six cases of Hyb‐thy preparation in six juvenile miniature swine. Two pigs received non‐manipulated cynomolgus monkey thymic cells that were isolated from an excised atrophic thymus via injection into their thymic lobes (Group 1). The remaining four received thymic cells that were isolated from non‐atrophic thymic glands (Groups 2 and 3). Pigs in Group 2 received unmanipulated thymic cells in one thymic lobe, as well as CD2‐positive cell‐depleted TEC‐enriched cells in the contralateral lobe. Pigs in Group 3 received TEC‐enriched cells alone. Results: All thymus‐injected pigs received tacrolimus and rapamycin until endpoint (POD16). We detected cynomolgus monkey TEC networks in pig thymus from Groups 1 and 3, while pigs in Group 2 rejected the thymic cells. We demonstrated the preparation of Hyb‐thy in pigs using tacrolimus plus rapamycin therapy. Conclusions: Our results suggest that the enrichment of TEC from the excised NHP thymus facilitated NHP TEC engraftment in pig thymus.